-2k-3=4k-15

Simple and best practice solution for -2k-3=4k-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2k-3=4k-15 equation:



-2k-3=4k-15
We move all terms to the left:
-2k-3-(4k-15)=0
We get rid of parentheses
-2k-4k+15-3=0
We add all the numbers together, and all the variables
-6k+12=0
We move all terms containing k to the left, all other terms to the right
-6k=-12
k=-12/-6
k=+2

See similar equations:

| -12=3r+3r | | -(6x-1)=0 | | 11-1/2y=3+6y | | |3n-4|=-1 | | 2u^2-5u-18=0 | | -6x+1=14x5 | | 12=-3(2x+2)+7x | | |3n-4|=1 | | 90=12x+42 | | 3x/4-7/5=2x/10 | | 0.1x-0.6x-14=1 | | -3a+3+4a=10-21 | | x(4)=2x | | 6x-10=4x+22 | | 2+5.7t-4.9t^2=0 | | 2=​2/m−7 | | 1.5t^2-24t=0 | | x+5=-81 | | 4f-16+2f=3f+11 | | x+2(x-7)=3x-7 | | 4r=21+2.50r | | (4x+9)+(4x+8)+(4x)=(4x)+4x)+(5x+6) | | F(x)=5/6x-15 | | 3z+15=48 | | 8x-2(3x-5)=24 | | 8(5x-3=6(-3x-4) | | -1/8c=-5/4 | | 2r-3/5=3 | | 3(x-4)=2x=6 | | 6x-12=18-8x | | (4x+9)+(4x+8)+(4x)=(4x)=(4x)+(5x+6) | | 0.7x-0.4(50+x)=-0.1(50) |

Equations solver categories